Influence of proprioceptive training based on ankle-foot robot on improving lower limbs function in patients after a stroke - Mao, Yajun; Gao, Zhenzhen; Yang, Hang; Song, Caiping (Frontiers in Neurorobotics, 2022)
Background Proprioception is important for our everyday activity, as it indicates the position, movement, and force on the body. This is important not only for ambulation but also for patients who are diagnosed with stroke. Objective This study aimed to evaluate the influence of proprioceptive training on lower limb function in patients after a stroke using an ankle-foot robot. Method In total, 60 adult participants who met the criteria were randomly divided into a control group and an experimental group. The control group (RG) was given regular physical activity, and the sensory training group (SG) was given proprioceptive training based on an ankle-foot robot, the rest being the same as RG. Measurements for 10-meter walking time (10MWT), the Berg Balance Scale (BBS), the Fugl-Meyer assessment of lower extremity (FMA-LE), and active range of motion (AROM), passive range of motion (PROM), and ankle joint sensitivity before and after 6 weeks of treatment (30 sessions; five times per week) were assessed. Results There was a significant decrease in both 10MWT and ankle joint sensitivity in both groups (p < 0.05), while there was a significant increase in BBS, FMA-LE, AROM, and PROM in both groups (p < 0.05). A significant relationship was identified between the two groups, the SG group had greater degrees of improvement compared to the RG group. Conclusion The proprioceptive training based on an ankle-foot robot could improve proprioception and effectively improve the motor function and walking ability in patients after a stroke. Proprioceptive strength training is recommended to be emphasized in the regular rehabilitation of patients after a stroke.